2013
DOI: 10.1017/s0950268813001738
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity of preterm infants of less than 33 weeks gestation without bronchopulmonary dysplasia: a 12-month follow-up of the CASTOR study cohort

Abstract: SUMMARYThe aim of this study was to describe the incidence and risk factors for respiratory morbidity during the 12-month period following the first respiratory syncytial virus (RSV) season in 242 preterm infants [<33 weeks gestational age (GA)] without bronchopulmonary dysplasia and 201 full-term infants (39-41 weeks GA) from the French CASTOR study cohort. Preterm infants had increased respiratory morbidity during the follow-up period compared to full-terms; they were more likely to have wheezing (21% vs. 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…Even though the majority of the data on the long-lasting impact of RSV have been based on studies of healthy term-born infants, limited studies have demonstrated increased risk of asthma [68], recurrent wheeze [34,69,70] and lung function impairments [66] in preterm children with a history of RSV-related hospitalisation during infancy. Early-life hospitalisation with RSV infection in preterm infants has been associated with more than twice the risk of ongoing respiratory morbidity, with wheezing rates ranging from 20.7 to 42.8%, 1–2 years following RSV-related hospitalisation compared to 4.1 to 23% following non-RSV related hospitalisation [43].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Even though the majority of the data on the long-lasting impact of RSV have been based on studies of healthy term-born infants, limited studies have demonstrated increased risk of asthma [68], recurrent wheeze [34,69,70] and lung function impairments [66] in preterm children with a history of RSV-related hospitalisation during infancy. Early-life hospitalisation with RSV infection in preterm infants has been associated with more than twice the risk of ongoing respiratory morbidity, with wheezing rates ranging from 20.7 to 42.8%, 1–2 years following RSV-related hospitalisation compared to 4.1 to 23% following non-RSV related hospitalisation [43].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Generally speaking, BW is one of several factors which may affect lung function and could predict future lung development. Usually this issue has been analyzed in children [6] in terms of very LBW, which is connected with many pre-and perinatal disturbances [2,3]. Our study was performed on a sufficiently large number of adult patients, and we attempted to demonstrate the influence of different BW quartiles on the most important spirometric parameters in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In the later years of life in these children we often observe worse ventilation parameters than in their peers with a normal BW [2]. This particular group of children often suffers from both infant respiratory distress syndrome and bronchopulmonary dysplasia (BD), which may be risk factors of chronic lung disease, although certain data suggests that ventilating disorders in children with LBW may be present independently of bronchopulmonary dysplasia BD [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have also found that premature newborns that received mechanical ventilation (MV) during the neonatal period showed greater risk of developing respiratory diseases like asthma and pneumonia in early childhood when compared to those that did not receive MV 13,14,15,16,17 . Neonatal MV was also associated with altered pulmonary function (spirometry) at 8-9 years 18 , as well as increased odds of asthma during childhood and adulthood 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%